2021
DOI: 10.52168/bjf.2021.33.08
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fish stocking density on growth and survival of Silver carp (Hypophthalmichthys molitrix) fry in Jashore, Bangladesh

Abstract: The experiment was operated in 9 consecutive weeks in nine earthen nursery ponds having the same area (0.09 acre) and depth (0.8 m). Seven days old fries of Silver carp (Hypophthalmichthys molitrix) were stocked at 4000, 5000 and 6000 fries/decimal in three treatments with three replications as T-1, T-2 and T-3, respectively to observe the growth and survival. At stocking, hatchlings were the same batch-rearing with an average length and weight of 0.44 ± 0.05 cm and 0.14 ± 0.05 mg, respectively. Wet mustered o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Previous studies have suggested adaptive production techniques such as floating bed vegetable cultivation and dike cropping (mainly for vegetables) in order to cope with changing climatic conditions (e.g., floods, waterlogging); this can eventually reduce vulnerabilities and increase food security [51][52][53]. Vegetable cultivation on pond dikes is an improved agricultural practice that ensures maximum use of a small household or farm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested adaptive production techniques such as floating bed vegetable cultivation and dike cropping (mainly for vegetables) in order to cope with changing climatic conditions (e.g., floods, waterlogging); this can eventually reduce vulnerabilities and increase food security [51][52][53]. Vegetable cultivation on pond dikes is an improved agricultural practice that ensures maximum use of a small household or farm.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetable cultivation on pond dikes is an improved agricultural practice that ensures maximum use of a small household or farm. In their study, Islam et al [53] showed that cultivation of different vegetables (e.g., pumpkins, cucumbers, bitter gourds, teasle gourds, broad beans) on pond dikes could enable higher profits from this farming system. Azad et al [54] conducted a study in coastal areas of Bangladesh, finding that many farmers grew vegetables on the dikes of their ponds (ghers).…”
Section: Discussionmentioning
confidence: 99%